Efficiency Estimation of Olefin Furnaces in Order to Provide Methods for Increasing the Efficiency - Jamaledin Binanejad; Amir Homayoon Meghdadi Isfahani (International Journal of Advanced Design and Manufacturing Technology, 2019)
Despite the growing trend in the petrochemical industry in the country, the industry has faced challenges and accomplishments. One of the most important challenges in the petrochemical industry is energy management in the refinery. Fajr Jam refinery is designed to refine part of sour gas produced from Phase 6 of South Pars gas field in Iran and the nominal capacity of gas refining at this site, to determine the factors affecting energy consumption in the ophthalmic furnaces, 104 and 109 kilns were selected and the following were monitored scientifically: monitoring of furnace wall temperature with thermography, furnace feed analysis, steak gas analysis and energy efficiency of furnaces. The results of this study showed that in the furnace 104, the design efficiency and real efficiency was 92.98 and 84.67, respectively and for the furnace 109, the design efficiency and real efficiency was 94.98 and 71.18, respectively. As a result, the amount of energy loss is high and should save energy consumption in these furnaces and improve efficiency: replacement of refractory refractories is also a replacement of insulation.